An all-weather solar cell that can harvest energy from sunlight and rain. (December 2016) - Tang, Qunwei; Zhang, Hongna; He, Benlin; Yang, Peizhi
Abstract: Future solar cells may produce electricity in all weathers. We present here a cost-effective and high-efficiency graphene based conducting composite tailored all-weather solar cell that can be actuated with raindrops and sunlight. Due to the formation of π-electron|cation double-layer pseudocapacitance at conducting composite/raindrop interface, the delocalized π-electrons on graphene can migrate along percolating pathways forward at spreading process and backward at shrinking periods, resulting in charging and discharging of the pseudocapacitor. The optimized solar cell yields a photoelectric conversion efficiency of 9.8% under simulated sunlight irradiation (air mass 1.5, 100 mW cm −2 ) as well as current over several microamps and voltage of hundreds of microvolts under simulated raindrops. This work could extend our knowledge of future all-weather solar cells. Graphical abstract: An all-weather solar cell is fabricated by integrating a graphene tailored conducting composite with a solar cell, yielding photoelectric conversion efficiency on sunny days and electric signals on rainy days. Highlights: An all-weather solar cell is created for harvesting energy from sun and rain. G-CB/PTFE conducting composite is utilized to replace graphene film. The G-CB/PTFE film has percolating pathways for creating EDL pseudocapacitor. The launched solar cell extend our knowledge of future all-weather solar cell.